Exploring health policy development in Europe - Wood-Ritsatakis, Anne. (Copenhagen : World Health Organization, Regional Office for Europe, 2000)
(NtOW^ HURAANGUJs
Includes bibliographical references.
Keywords: medical policy -- Europe; health policy -- trends